Find it online : - Schlein, Alan M (Facts on Demand Press, 2004)
Contain includes: which search engines work best for which kinds of questions, how to get the fewest possible sites from a search with the greatest likelihood that they will be helpful to you, which sources of information to go to directly without a search first; how to assess the credibility of a source. How to get things for free that most people pay for, when to spend money to save time, how to manage your e-mail to spend less time on it.